Improving The Evaluation System Of Risk And Return Indicators In Private Capital Investments In Uzbekistan - Fayziyev Umurkul Shuxratovich; Yo‘lbarsova O‘g‘iloy Muhammadshohid qizi (Next Scientists International Journal JME, 2026)
This study examines the improvement of the evaluation system for risk and return indicators in private capital investments in Uzbekistan. The research focuses on the growing importance of private capital as a source of economic development, innovation, and business expansion in emerging economies. In recent years, Uzbekistan has implemented significant economic reforms aimed at attracting domestic and foreign investment, improving the business environment, and strengthening financial markets. However, investors still face challenges related to market uncertainty, regulatory changes, financial transparency, and risk assessment mechanisms.The paper analyzes the theoretical foundations of investment risk and return evaluation and explores international approaches used in private equity and venture capital investments. Particular attention is given to the identification of financial, operational, legal, political, and macroeconomic risks affecting private capital investments in Uzbekistan. The study also evaluates existing methods for measuring investment performance, including profitability indicators, risk-adjusted return models, and portfolio diversification techniques.Based on comparative analysis and current market conditions, the research proposes an improved framework for evaluating investment efficiency and risk management in Uzbekistan’s private capital sector. The proposed system integrates quantitative and qualitative indicators, enhances transparency in investment decision-making, and supports sustainable capital allocation. The findings of the study may be useful for policymakers, investment funds, financial institutions, and private investors seeking to increase investment attractiveness and ensure long-term economic stability in Uzbekistan.